Enhanced liquid–gas mixing due to pulsating injection. (31st January 2015) - Grosshans, H.; Szász, R.-Z.; Fuchs, L.
Highlights: We simulate pulsed sprays and jets. The key results previous experimental and analytical works could be recovered. The pulse tail-speed was analyzed depending on different gas and liquid parameters. Increasing the injection frequency showed a significant improvement in the mixing. The main mechanisms of enhanced mixing were identified and discussed. Abstract: This paper considers the effects of intermittent injection of a liquid jet or spray on the initial break-up and mixing of one fluid with the surrounding ambient fluid. The aim of the analysis is to describe the physical process and indicate the mechanisms that control the mixing under different flow conditions (time-dependent injection and its frequency relative to the time scales of the flow) and fluid properties (density ratio), Schmidt number for a single phase case which is studied for comparison, or the Weber number for the two-phase cases. The computations use Large Eddy Simulation (LES) to account for turbulence, and either Volume Of Fluid (VOF) for the initial break-up or Lagrangian Particle Tracking (LPT) with droplet break-up model in the case of liquid droplets injected into the ambient gas. The results show that, depending on the physical properties of the liquid and ambient gas, the initial break-up and turbulent mixing can be enhanced substantially with intermittent injection. The numerical modeling is validated by recovering key results of experimental and analytical works. It can be observed that a main effect during the mixing is the suction of ambient fluid at the tail of the injected liquid, which depends on the fluid properties. Increased injection frequency shows to increase the mixing significantly during the initial transient phase.